2002
DOI: 10.1523/jneurosci.22-03-01146.2002
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Effects of Cannabinoids Are Mediated by μ-Opioid and κ-Opioid Receptors

Abstract: Repeated THC administration produces motivational and somatic adaptive changes leading to dependence in rodents. To investigate the molecular basis for cannabinoid dependence and its possible relationship with the endogenous opioid system, we explored ⌬9-tetrahydrocannabinol (THC) activity in mice lacking -, ␦-or -opioid receptor genes. Acute THCinduced hypothermia, antinociception, and hypolocomotion remained unaffected in these mice, whereas THC tolerance and withdrawal were minimally modified in mutant anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
209
1
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(231 citation statements)
references
References 45 publications
11
209
1
10
Order By: Relevance
“…Surprisingly, THC, as well as synthetic cannabinoid agonists, like CP 55,940 (McGregor et al, 1996), WIN 55,212-2 (Chaperon et al, 1998 and HU 210 (Cheer et al, 2000), generally induce conditioned place avoidance or aversion rather than place preference in rats (Parker and Gillies, 1995;Sanudo-Pena et al, 1997;Hutcheson et al, 1998;Mallet and Beninger, 1998) and mice (Valjent and Maldonado, 2000), although THC-induced conditioned place preferences have been reported at limited dose-ranges and under restricted experimental conditions in Long Evans rats and in mice (Lepore et al, 1995;Valjent and Maldonado, 2000;Ghozland et al, 2002) and CP 55,940-induced conditioned place preferences have been reported in Wistar rats (Braida et al, 2001a).…”
Section: Subjective and Motivational Effects Of Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, THC, as well as synthetic cannabinoid agonists, like CP 55,940 (McGregor et al, 1996), WIN 55,212-2 (Chaperon et al, 1998 and HU 210 (Cheer et al, 2000), generally induce conditioned place avoidance or aversion rather than place preference in rats (Parker and Gillies, 1995;Sanudo-Pena et al, 1997;Hutcheson et al, 1998;Mallet and Beninger, 1998) and mice (Valjent and Maldonado, 2000), although THC-induced conditioned place preferences have been reported at limited dose-ranges and under restricted experimental conditions in Long Evans rats and in mice (Lepore et al, 1995;Valjent and Maldonado, 2000;Ghozland et al, 2002) and CP 55,940-induced conditioned place preferences have been reported in Wistar rats (Braida et al, 2001a).…”
Section: Subjective and Motivational Effects Of Cannabinoidsmentioning
confidence: 99%
“…Most of the evidence for a role of endogenous opioid systems in the modulation of the reinforcing or rewarding effects of THC or cannabinoids is indirect and comes from behavioral studies of locomotion (Ghozland et al, 2002) or electrical brain stimulation reward (Gardner et al, 1989) or from in-vivo brain microdialysis studies in rodents (Chen et al, 1990;Tanda et al, 1997). More direct evidence for a role of opioid neurotransmitter systems in the modulation of the reinforcing effects of cannabinoids comes from recent rodent drug self-administration studies in which naloxone pretreatment reduced intravenous drug self-administration behavior maintained by the synthetic cannabinoid CB 1 receptor agonists WIN 55,212-2 and HU-210 (Navarro et al, 2001) and CP 55,940 (Braida et al, 2001a;.…”
Section: Self-administration Of Cannabinoids By Laboratory Animalsmentioning
confidence: 99%
“…Thus, conditioned place preference induced by THC or WIN 55, can only be revealed in mice if they received a previous injection of the drug 24 h before the first conditioning day (Valjent and Maldonado, 2000;Castañé et al, 2004). Studies with genetically modified animals have provided further support to this hypothesis and have revealed the specific involvement of the k/ dynorphin system in such an initial aversive response of cannabinoids (Zimmer et al, 2001;Ghozland et al, 2002;Cheng et al, 2004). Thus, conditioned place preference to THC could be revealed in k knockout mice without avoiding the dysphoric consequences of the first exposure to the drug (Ghozland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous opioid system seems to play an important role in the different effects produced on the reward circuit after cannabinoid administration. Accordingly, both pharmacological and genetic studies have provided evidence that the rewarding effects of cannabinoids are mediated by the activation of m-opioid receptors, whereas the stimulation of k-opioid receptors (KORs) by opioid peptides derived from pro-dynorphin seem to mediate their aversive effects (Ghozland et al, 2002;Zimmer et al, 2001). Moreover, several studies suggest that the k/dynorphin system opposes drug-rewarding effects, giving support to the idea that KORs could act as a possible pharmacotherapy for drug dependence (for a review, see Hasebe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…8 The CB 1 receptors have been strongly coupled to endogenous opioid systems especially in relation to reward and addictive behaviors. [9][10][11][12][13][14] The opioid system (endogenous ligands and receptors) is involved in a wide variety of neuronal functions including pain perception, cognition, emotional regulation and addictive behaviors (for a review see 15 ). There are two major groups of endogenous opioid neuropeptides, which are strongly involved in drug-dependent processes, enkephalins and dynorphins.…”
Section: Introductionmentioning
confidence: 99%